USABILITY TESTING OF A MULTIMEDIA APPROACH FOR SELECTING RISK ASSESSMENT METHODS - , Amarria Dila Sari, Dr. Alva Edy Tontowi, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Safety practitioners use several risk assessment methods to analyze manual material handling. A multimedia application was developed with Macromedia Flash Player to help selecting risk assessment methods in Manual Material Handling tasks. This study intends to help safety practitioners to identify and select the appropriate methodologies for Manual Material Handling risk assessment and for supporting the decision-making process, in what regards the risk assessment method selection. Therefore, a simple interface was developed in this study. The Interview method was used to develop the previous multimedia application (application 1). There were 9 recommendations in the new multimedia application (application 2), which were text justified deleting list table, changing the font size, changing texts, adding the âbackâ button, changing icons, making the list of texts, making definition of three classifications, making the classification table. Usability testing was used to evaluate the interfaces of the multimedia application by comparing the previous application and the new one. This analysis was carried out considering the easiness, effectiveness, efficiency, and satisfaction on the applications. Based on the performance measurement, application two was better than application one. The effectiveness in application two was 4% better than in application one, the efficiency was one minute faster, and the satisfaction was 8% better. From the entire test concerning the relationship between effectiveness and background of participants, it can be concluded that there were no relationships between prior knowledge in Manual Material Handling, prior knowledge in risk assessment methods, education levels, and study background with the effectiveness in applications one and two. It also revealed that there were no barriers in using both applications.